Anatomical Structure of Surian Wood (Toona sinensis Roem) - Atmawi Darwis; Imam Wahyudi; Ratih Damayanti (Masyarakat Peneliti Kayu Indonesia, 2012)
Surian wood (Toona sinensis Roem) is one species of wood that is easily found in Indonesia, especially in West Java. The purpose of this study was to descriptively and quantitatively observe the anatomical structure of surian wood. The wood was collected from Sumedang regency, West Java. The results showed that this wood had oval to round shaped vessels and some of them contain a reddish brown liquid that causes a characteristic odor due to axial intersellular canals. The vessels were mostly solitary and arranged to follow the pattern of the porous ring. There were septate fibers indicated. Axial parenchyma cells were included in the category of paratracheal vasisentrik and marginal bands in the early wood. The ray composition consists of upright and procumbent cells. In the ray cell, there are prismatic crystals in rhomboidal or octahedral shape. Based on the dimensions of fibers, this wood has first-class fiber quality for pulp and paper.Key words: anatomical structure, fiber dimension, fiber quality, Toona sinensis